Estimation of Longitudinal and Transverse Elastic Moduli of Native Brazilian Woods by Static Bending Tests - Fabricio da Silva Aguiar; Guilherme dos Santos Silva; Herisson Ferreira dos Santos; Elvys Dias Reis; Francisco Antonio Rocco Lahr; André Luis Christoforo (BioResources)
Wood plays an essential role in civil construction due to its structural and sustainable properties. The longitudinal (E) and the transverse (G) modulus of elasticity are crucial for designing beams under bending, where combined deformations occur due to normal and shear stresses. However, the estimation of G for native Brazilian species still lacks standardized experimental procedures, with the simplified normative relation G = E/16 being commonly adopted. This study aims to estimate both E and G based on the Euler-Bernoulli and Timoshenko beam theories through three-point and four-point static bending tests. Four native Brazilian species and five ratios between the length and height of the cross-section (L/h) were analyzed. The results showed that, for L/h ratios below 18, the apparent modulus of elasticity was significantly affected by shear effects, exhibiting reductions of up to 18.47%. The E/G ratio ranged from 14.84 to 21.15, corresponding to a reduction of up to 7% and an increase of up to 32%, respectively, about the value proposed by ABNT NBR 7190-1 (2022). These results highlight the importance of considering specimen proportions and shear effects in the estimation of wood elasticity moduli obtained from bending tests.